MENUMBUHKAN MODERASI BERAGAMA SEJAK DINI: PERAN EDUKATIF GURU PAI di SMP MUHAMMADIYAH 3 KUTOREJO MOJOKERTO - Ainun Nadlifa; Saifuddin; Justsinta Sindi Alivi (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This research was carried out with the aim of describing and analyzing the role, process and results of instilling religious motherhood attitudes by PAI teachers in students at SMP Muhammadiyah 3 Kutorejo. This research applies qualitative research with a case study approach. The subjects of the study were PAI teachers and students of Muhammadiyah 3 Kutorejo Junior High School. Data collection through observation, interviews, and documentation. The data collection technique goes through three stages: data reduction, data presentation, and conclusion drawn. The results of the study show that: First, the role of PAI teachers in instilling religious moderation attitudes in students at SMP Muhammadiyah 3 Kutorejo is as: educators, supervisors, role models. The second process of cultivating religious moderation attitudes at SMP Muhammadiyah 3 Kutorejo is through: PAI learning materials on moderate attitudes, morning habit of Dhuha prayers and reading short letters, Sunday Morning Public Recitation (PUAP), Gemajusa/BTQ, Darul Arqom. The three results of instilling a moderation attitude in students are: punctuality during worship, high social concern, growth of tolerance, and obedience and obedience to school regulations, accommodating to local culture.